Meningkatkan Hasil Belajar PKN dengan Model Pembelajaran Inkuiri pada Siswa Kelas IX SMP Negeri 14 Bandar Lampung - Wahyudin, Wahyudin (Lentera: Jurnal Ilmiah Kependidikan, 2015)
Enforcement Kurikulum Tingkat Satuan Pendidikan (KTSP) led subjects Pancasila and Citizenship Education (Civics) undergoes many changes that the charge material contained many concepts and no longer contains normative. In addition, usually only educators determine the materials and methods of teaching so that students activity is limited to listening, recording, and answered questions. To overcome these problems, the authors conducted a classroom action research (PTK) in SMPN 14 Bandar Lampung in August-September 2011 through inquiry learning model. The object of this study were students of class IX-5 of 40 people. PTK includes the following activities: (1) planning, (2) implementation, (3) observation, and (4) reflection. PTK data collection techniques through observation, interviews, documentation, and testing. The data analysis using descriptive analysis while data validation using data triangulation technique. The result showed that the inquiry learning model can improve learning outcomes Civics amounted to 24.4%, which is calculated based on average scores on the observation during the PTK in research.